Epidemiology of Blindness From Facial Trauma: A Multi-Centre Nigerian Study. Issue 1 (March 2023) - Famurewa, Bamidele A.; Oginni, Fadekemi Olufunmilayo; Adewara, Bolajoko A.; Fomete, Benjamin; Aniagor, Chukwudi; Aluko-Olokun, Bayo; Morgan, Regina E.; Amedari, McKing I.
Study Design: This is a multi-centre retrospective study. Objective: To determine the prevalence of blindness and pattern of facial trauma associated with blindness among Nigerians. Methods: A multi-centre retrospective study of all patients with facial trauma resulting in blindness, that were co-managed by maxillofacial surgeons and ophthalmologists in 4 Nigerian public tertiary hospitals between January 2010 and December 2019 was undertaken. Data was analysed by IBM SPSS Statistics (version 21.0 for windows, IBM© Inc, Chicago, IL). Results: Of 2070 patients who presented with major facial injuries during the study period, 61 eyes of 56 (2.7%) patients were blind. Blindness was bilateral and unilateral in 5 (8.9%) and 51 (92.1%) patients, respectively. The mean age (SD) at presentation was 36.2 (16.6) years, and 47 (83.9%) of these patients were males. Road traffic accident (n = 27; 48%) was the commonest mechanism of facial trauma, the cheek (n = 18; 40.9%) was the commonest site of associated soft tissue injury and zygomatic complex fracture (n = 19; 24.1%) was the commonest related fracture. Globe rupture (n = 34; 55.7%) was the leading cause of blindness. Enucleation (n = 7; 13.2%) and evisceration (n = 22; 41.5%) were performed on 29 eyes of which 12 (41.4%) patients had ocular prosthesis post-operatively. Conclusions: Blindness was recorded in 2.7% of Nigerians with facial trauma. The commonest mechanism of trauma and cause of blindness in at least one eye were road traffic accident and globe rupture, respectively. Eye removal surgery was necessary in about half of the blind eyes.